Dramatic loss of microbial viability in bentonite exposed to heat and gamma radiation: implications for deep geological repository - Bartak, Deepa; Šachlová, Šárka; Kašpar, Vlastislav; Říha, Jakub; Dobrev, David; Večerník, Petr; Hlaváčková, Veronika; Matulová, Michaela; Černá, Kateřina (World journal of microbiology & biotechnology, 2024)
Bentonite is an integral part of the engineered barrier system (EBS) in deep geological repositories (DGR) for nuclear waste, but its indigenous microorganisms may jeopardize long-term EBS integrity. To predict microbial activity in DGRs, it is essential to understand microbial reactions to the early hot phase of DGR evolution. Two bentonites (BCV and MX-80) with varied bentonite/water ratios and saturation levels (compacted to 1600 kg.m- 3 dry density/powder/suspension), were subjected to heat (90-150 °C) and irradiation (0.4 Gy.h- 1) in the long-term experiments (up to 18 months). Molecular-genetic, microscopic, and cultivation-based techniques assessed microbial survivability. Exposure to 90 °C and 150 °C notably diminished microbial viability, irrespective of bentonite form, with negligible impacts from irradiation or sample type compared to temperature. Bentonite powder samples exhibited microbial recovery after 90 °C heating for up to 6 months but not 12 months in most cases; exposure to 150 °C had an even stronger effect. Further long-term experiments at additional temperatures combined with the mathematical prediction of temperature evolution in DGR are recommended to validate the possible evolution and spatial distribution of microbially depleted zones in bentonite buffer around the waste canisters and refine predictions of microbial effects over time in the DGR.
Keywords: Microbial limiting factors; záření gama; Gamma Rays; radioaktivní odpad; Deep geological repository; Radioactive waste disposal; mikrobiální viabilita; vysoká teplota; Bentonite buffer; Hot Temperature; Bentonite; Extremophiles; Gamma radiation; půdní mikrobiologie; bentonit; Elevated temperature; Bacteria; Microbial Viability; Radioactive Waste; Soil Microbiology